Serum Triglyceride and Total Cholesterol in Association with IGT: A Case Control Study among Bangladeshi Adults in Jashore City - Akhter, Marufa; Datta, Subhra Prakash; Ferdous, Mokerroma; Era, Hasnat Silvi (IAHS Medical Journal, 2022)
Background: Existing researches demonstrated that hyperglycemia was associated with elevated serum Triglyceride (TG) and Total Cholesterol (TC). It is imperative to identify prediabetic conditions like Impaired Glucose Tolerance (IGT) for prevention or delay in the development of Type 2 Diabetes Mellitus (T2DM). It is also quite comprehensible that early diagnosis of IGT provides opportunity for effective interventions like dietary and lifestyle modification.The primary objective of this study was to investigative the association of serum TG and TC with IGT in an urban area of Bangladesh. Materials and methods: This study was an observational study with a case-control design carried out on a total of 102 IGT subjects and 150 age, Body Mass Index (BMI) and Waist-Hip Ratio (WHR) matched control subject, over 2 years of time.Biochemical tests including Fasting Plasma Glucose (FPG) plasma glucose2 hours after 75 grams glucose load (2 h PG) serum TC and serum TG using slandered procedure. IBM SPSS Statistics 25 version was used for statistical analysis. Results: Serum TG level was significantly high in IGT cases when compared with controls.Serum TC was also different in cases when compared to controls, but was not significant statistically. Conclusion: Higher level of serum TG is associated with IGT. The association of high serum TC and IGT was not decisive. IAHS Medical Journal Vol 5(1), June 2022; 12-15